A 10-year Study of Bobwhite Quail Movement Patterns - Gladys F. Smith; Forest E. Kellogg; William R. Davidson; W. Mack Martin (National Quail Symposium Proceedings, 2017)
The movement patterns of 676 bobwhite quail (Colinus virginianus) on two study areas on Tall Timbers Research Station in northern Florida were studied during a 10-year period. Eighty-six percent of the quail moved no more than 400 m from their first documented location in a one- to five-year period. Ninety-eight percent moved less than 800 m. Movements greater than 1,000 m occurred but were rare. There were no substantial differences in the annual movements of males and females or immatures and adults; however, the few birds which made longer movements ()800 m) tended to be immature males. The average distance an individual quail moved during a two-week shooting period was greater than the distance moved during the preceding two-week trapping period, but the average difference was only 82 m and therefore insignificant from a practical viewpoint. Movements during shooting averaged 150 m and were not extensive enough to force quail off the study area. Egress and ingress were minimal and approximately balanced. The population was much less mobile than bobwhite populations in other portions of the species' range.